Effects of Smoking Opportunity on Attentional Bias in Smokers - Wertz, Joan M. (2001)
The emotional Stroop task was used to examine the influence of opportunity to smoke on attentional bias to smoking-related stimuli. At the outset of the study, 92 nicotine-deprived smokers were told that they (a) would, (b) would not, or (c) might be able to smoke during the experiment. Next, participants completed an emotional Stroop task, in which they were presented with smoking-related or -unrelated words in an unblocked format. Smokers demonstrated interference to the smoking words, relative to matched neutral words, F(1, 87) = 18.0, p < .0001. Moreover, smoking opportunity affected the degree of interference, F(2, 87) = 4.35, p < .02, with participants who had been told they would be able to smoke during the study showing the most interference. The results suggest that smoking opportunity affects the salience of smoking-related stimuli among nicotine-deprived smokers.